Determination of flood vulnerability level based on different numbers of indicators using AHP-GIS - I Gusti Agung Putu Eryani; Made Widya Jayantari; Suzana Ramli (Universitas Mercu Buana, 2024)
approaches to a flood management strategy. One of the most important steps is identifying flood-vulnerable areas. A flood vulnerability assessment is necessary to identify the areas. Currently, research on flood vulnerability assessment uses different indicators to determine the flood vulnerability level. However, it is unknown how the number of indicators used to assess flood vulnerability affects the results. This research aimed to determine the effect of the number of indicators used in estimating flood vulnerability using the AHP-GIS method on the resulting flood vulnerability level. Therefore, this research analyzed the weight of each indicator for five scenarios using the AHP method. This step is continued using GIS to create an overlay map to calculate each scenario's flood hazard index. The indicators used to determine the flood vulnerability index include elevation, slope, flow accumulation, drainage distance, land use, soil type, and annual rainfall intensity. The results showed that the reduction of indicators from seven to six caused the areas with moderate and very high levels of flood vulnerability to increase, while those with high levels decreased. Meanwhile, the reduction from six to five indicators caused the areas with low and moderate vulnerability to reduce, while those with high and very high levels increased. It was also discovered that when the indicators were changed from five to four, the areas with moderate and high vulnerability increased while those with very high levels decreased.